Facile synthesis of hierarchical nickel (III) oxide nanostructure: A synergistic remediating action towards water contaminants. (1st April 2018) - Dey, Sayan; Podder, Soumik; Roychowdhury, A.; Das, Dipankar; Ghosh, Chandan Kr.
Abstract: Heavy metal ion removal from consumable water is an indispensable need to maintain healthy life. Therefore cost effective and highly efficient sorbents are strongly needed to pose threat to real water pollution. Nanomaterials are widely used to maintain clean aqueous system in a very cost effective way with high removal efficiency. In this present work, pure coral like Ni2 O3 nanostructures were prescribed for Cr(VI) remediation which were prepared by two step synthesis procedure at room temperature. The single hierarchical morphology as confirmed from HRTEM (size∼200 nm) were subjected to toxic Cr(VI) ion removal experiments. They were found to remove ∼65% Cr(VI) ions that was higher than that of pure Ni2 O3 nanoparticles of comparable size. The enhanced properties were explained on the basis of the defect states present within the nanostructure, investigated by positron annihilation lifetime spectroscopy (PALS). It was found that the hierarchical nanostructure had more number of di-vacancies and vacancy-clusters as compared to the particles. On performing isotherm fitting, it was found that the coral like morphology had a high heterogeneity factor that aided to a high adsorption rate when compared to the pure Ni2 O3 nanoparticles (which had a homogenous surface). The synthesized nanostructure was severely toxic to bacterial community having minimum inhibitory concentration (MIC) of ∼300 μg/L. Also the nanostructure exhibited dual functionality towards Cr(VI) and bacteria contaminated water at 200 μg/ml. The maximum Cr(VI) removal efficiency for this dual system is found to be 39% whereas antibacterial activity was turned out to be 30% which was extensively higher than that of toxic Cr(VI) ions. A plausible mechanism for the dual functionality was also predicted. Graphical abstract: Image 1 Highlights: Room temperature synthesis of pure anhydrous Ni2 O3 nanocoral and its Cr(VI) removal. Vacancy clusters in Ni2 O3 nanocoral promotes 65% Cr(VI) removal. Ni2 O3 nanocoral exhibited excellent stability and repeatability after multiple usages. Ni2 O3 exhibited dual activity towards Cr(VI) and bacteria contaminated water. Plausible mechanism is presented to analyse dual activity of Ni2 O3 nanocoral.